Anterolateral approach to the upper cervical spine: Case report and operative technique. Issue 9 (26th May 2015) - Song, Yohan; Tharin, Suzanne; Divi, Vasu; Prolo, Laura M.; Sirjani, Davud B.; Andersen, Peter
Abstract Background Transcervical approaches to the upper cervical spine are challenging because several upper anterior neurovascular structures need to be displaced to provide access. Although various techniques have been described, the anterolateral approach is one of the safest and most effective methods available to access the anterior C2–C3 disc space. Despite the approach's efficacy, however, it can cause postoperative complications because of, at least partly, the inter‐surgeon differences in the methods by which the larynx and hypopharynx are displaced medially. Methods and Results We present a case report of a patient treated with a modified anterolateral approach to C2–C3. The approach provided excellent visualization while protecting vital structures. The patient recovered without any postoperative dysphagia or other surgical complications. Conclusion The anterolateral approach to C2–C3 described herein safely protects the contents of the submandibular triangle while providing a wide exposure for direct access to the C2–C3 disc space. © 2015 Wiley Periodicals, Inc. Head Neck 37: E115–E119, 2015